(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Badi ceramics have endless aesthetic and functionalcapabilities. Its artistic and technical qualities can be used in architecture, monumental and decorative art, sculpture and designn. A rich historical experience convinces us that ceramism is subject to solving complex problems of synthesis with architecture. In modern art, the desire for a variety of materials used for all artists is more pronounced in t obora